The Role of Vitamin C in Management of Hypertension: A systematic review - Rivani Sintia Suratman; Harnavi Harun; Drajad Priyono; Deka Viotra (Indonesian Journal of Kidney and Hypertension, 2025)
Background: Vitamin C is an antioxidant that can reduce oxidative stress. Oxidative stress has been thought to play an important role in the pathophysiology of hypertension. Studies have looked at Vitamin C as a supplement to treat hypertension. Vitamin C’s use as a complementary treatment for hypertension remains controversial, nevertheless. This study aims to evaluate vitamin C’s contribution to the treatment of hypertension. Objective: To conduct a literature review that examines how vitamin C (VC) supplements affect hypertension. Methods: This research uses a systematic literature review (SLR) approach with sources obtained from various online databases, including PubMed, Cochrane Library, EBSCO, and Elsevier, using the keywords "vitamin C" and "Hypertension". The selected articles were in accordance with the inclusion and exclusion criteria and discussed the role of vitamin C in lowering blood pressure in hypertension. Results: All the articles displayed fair methodological quality and reported significant positive effects of vitamin C for lowering blood pressure. Conclusions: Vitamin C can help decrease blood pressure as a complementary treatment.